Problematika Guru Dalam Implementasi Kurikulum Merdeka Pada Pembelajaran Matematika Kelas VII Di SMPN 20 Simbang - Muhammad Akbar M.; Ernawati; Dedy Setyawan (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2023)
This qualitative research aims to describe the problems that teachers face in implementing the Merdeka Curriculum in the 7th-grade mathematics classes at SMPN 20 Simbang. Teachers encounter several issues, such as the challenge of adapting to the new concepts and implementation of the Merdeka Curriculum, developing modules, and strengthening the Pancasila student profile (P5), as well as adjusting teaching materials to meet the students' needs. The contributing factors to these problems include a lack of comprehensive understanding of the Merdeka Curriculum, limitations in terms of time and technological facilities, and delays in the provision of books as teaching materials. Teachers have made various efforts to address these issues, such as identifying obstacles during the implementation of the Merdeka Curriculum, attending training, participating in the Subject Teacher Forum (MGMP), and collaborating with fellow teachers and supervisors. They have also implemented collaborative and project-based teaching methods as well as technology to enhance student interactivity and self-reliance. This research highlights the challenges teachers face in implementing the Merdeka Curriculum and the efforts they have made to overcome these challenges. It is expected that the findings of this research will contribute to improving the quality of education at SMPN 20 Simbang and serve as a reference for future research in this field.